Acceptability and feasibility of two interventions in the MooDFOOD Trial: a food-related depression prevention randomised controlled trial in overweight adults with subsyndromal symptoms of depression. Issue 9 (15th September 2020) - Owens, Matthew; Watkins, Edward; Bot, Mariska; Brouwer, Ingeborg Annemarie; Roca, Miquel; Kohls, Elisabeth; Penninx, Brenda; van Grootheest, Gerard; Cabout, Mieke; Hegerl, Ulrich; Gili, Margalida; Visser, Marjolein
Abstract : Objectives: We report on the acceptability, feasibility, dose-response relationship and adherence of two nutritional strategies to improve mood (multinutrient supplements; food-related behavioural activation (F-BA)) studied in a randomised controlled depression prevention trial (the Multi‐country cOllaborative project on the rOle of Diet, Food‐related behaviour, and Obesity in the prevention of Depression (MooDFOOD) Trial). We also assessed baseline determinants of adherence and assessed whether better adherence resulted in lower depressive symptoms. Design: Randomised controlled trial with a 2×2 factorial design conducted between 2015 and 2017. Setting: Germany, the Netherlands, UK and Spain. Participants: Community sample of 1025 overweight adults with elevated depressive symptoms without a current episode of major depressive disorder. Main eligibility criteria included age (18–75 years), being overweight or obese, and having at least mild depressive symptoms, shown by a Patient Health Questionnaire Score of ≥5. A total of 76% of the sample was retained at the 12-month follow-up. Interventions: Daily nutritional supplements versus pill placebo or an F-BA therapy, delivered in individual and group sessions versus no behavioural intervention over a 1-year period. Primary and secondary outcome measures: Primary outcome: self-reported acceptability of the interventions. Secondary outcomes: adherence and self-reported depressive symptoms. Results: Most participants reported that the F-BA was acceptable (83.61%), feasible to do (65.91%) and would recommend it to a friend (84.57%). Individual F-BA sessions (88.10%) were significantly more often rated as positive than group F-BA sessions (70.17%) and supplements (28.59%). There were statistically significant reductions in depressive symptoms for those who both adhered to the F-BA intervention and had a history of depression (B=−0.08, SE=0.03, p = 0.012) versus those who had no history of depression. Supplement intake had no effect on depressive symptoms irrespective of adherence. Conclusions: F-BA may have scope for development as a depression prevention intervention and public health strategy but further refinement and testing are needed. Trial registration number: NCT02529423 .